Protection of Fecal Microbiota Transplantation in a Mouse Model of Multiple Sclerosis. (5th August 2020) - Li, Kanglan; Wei, Shouchao; Hu, Li; Yin, Xiaojian; Mai, Yingren; Jiang, Chunmei; Peng, Xiaoping; Cao, Xingxing; Huang, Zhongkai; Zhou, Haihong; Ma, Guoda; Liu, Zhou; et al.
Abstract : Given the growing evidence of a link between gut microbiota (GM) dysbiosis and multiple sclerosis (MS), fecal microbiota transplantation (FMT), aimed at rebuilding GM, has been proposed as a new therapeutic approach to MS treatment. To evaluate the viability of FMT for MS treatment and its impact on MS pathology, we tested FMT in mice with experimental autoimmune encephalomyelitis (EAE), a mouse model of MS. We provide evidence that FMT can rectify altered GM to some extent with a therapeutic effect on EAE. We also found that FMT led to reduced activation of microglia and astrocytes and conferred protection on the blood-brain barrier (BBB), myelin, and axons in EAE. Taken together, our data suggest that FMT, as a GM-based therapy, has the potential to be an effective treatment for MS.